The Constitutional Right to Health Protection in Belarus - Shupitskaya, Aksana (Medicine, Law & Society, 2020)
The article analyzes the constitutional right enshrined in the Fundamental law of the Belarusian state, its Constitution, - the right to health protection. The purpose of the research is to analyze the relevant legal regulations and the problems associated with implementing the right to health protection in the modern Belarus. The paper will examine the constitutional basis of the right to health protection in Belarus, its essence and nature, normative legal acts regulating the analyzed right, problems and prospects of its implementation in light of the current conditions of the Belarusian state. The author considers the constitutional legal principles and constitutional legal norms as the basis of the right to health protection and reveals the essence of the analyzed right. The conclusion substantiates the idea that detailed regulation of the right to health protection is carried out at the level of normative legal acts of the Republic of Belarus adopted by various state bodies. The state of realization of the right to health protection is determined by socio-economic, political and other factors. Identifying a number of problems related to ensuring the right to health protection, the researcher analyzes the prospects for its further development in the Republic of Belarus.
Keywords: constitution; constitutional principles and norms; accessibility and quality of medical care problems of realization of the right to health protection; protection, prospects for the development of the right to health protection